Assessment of Public Perception and Awareness on Water Management Practices in Maharashtra - Dadve , Jagannath V.; Turkar , Virendra B. (International Journal of Membrane Science and Technology, 2023)
Water management in Maharashtra faces complex challenges due to its varied climatic conditions and diverse population. This research aims to fill a critical gap by assessing public perception and awareness regarding existing water management practices in both urban and rural areas of the state. Through a survey-based methodology, the study explores the public's understanding of water scarcity, policy effectiveness, and their roles in sustainable water management. The findings indicate a significant disparity in awareness levels between rural and urban communities and offer insights into the public's willingness to engage in water-saving behaviors. These results have important implications for policymakers, suggesting a need for targeted educational and awareness campaigns. By understanding public perception and awareness, this study hopes to contribute to the development of more effective, community-oriented water management strategies in Maharashtra.